Konsep ‘Ilm Dalam Al-Qur’an - Aini, Lia Qurrota (Al-Bayan: Jurnal Ilmu al-Qur'an dan Hadist, 2018)
The Qur'an is like a gem that emits many rays of different colors. Therefore, we need to understand it with many kinds of knowledge. In the Qur'an, the discussion of various sciences and its meanings is 855 times as a process of knowledge and the object of knowledge. This discussion triggers the jâhilîyah people whose majority of the population uses the knowledge of mere conjecture and personal experience and ethnicity. Whereas in the Qur'an itself, knowledge is something given by God based on His truth and guidance. Because of the many discussions related to science, it is necessary to analyze semantic studies.